Optimizing Product Downstream and Management of Gambir Liquid Waste in Sopang Micro, Small and Medium Enterprises, Limapuluh Kota Regency - Sari, Risma; G, Gusfiyesi; Elisma, Netri; Prasada, Taufik Eka; D, Dartini; Bahar, Imelda; Asria, Merry (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
A series of Community Service activities has been carried out, focusing on assisting the downstream processing of gambir products and liquid waste in Micro, Small, and Medium Enterprises, as well as in the Gambir Farmers Association in Mungka District, Fifty Cities Regency. This activity was motivated by the challenges faced by members of the association, who produce gambir soap, gambir tea, and catechins that are not yet free from tannins. Unfortunately, the gambir soap produced lacks market value, has unappealing packaging, and does not provide optimal benefits to users, leading to decreased buyer interest. Additionally, the liquid waste generated from gambir production has not been adequately managed or treated to be environmentally friendly. Prior to the implementation of activities at the partner location, preparations were made, including sampling wastewater as a model for treating gambir production wastewater, clarifying wastewater, and enhancing the process of making gambir-based soap in the chemistry analysis laboratory at the ATI Polytechnic in Padang. In this activity, we aimed to provide solutions by broadening the partners' understanding of the downstream processing of gambir products and waste. Three key issues were addressed: catechin isolation, the production of catechin-based beauty soap, and the treatment of liquid waste from gambir production. The downstream processing of gambir products into more commercially valuable items is expected to provide solutions, while the liquid waste can eventually be processed into clean water, with the residue being converted into fertilizer. The activity was attended by 40 members of the Gambir Farmers Association, as well as the village head of Talang Maur, local officials, and the association's management.